Expressão heteróloga de abaecina de Apis mellifera em Pichia pastoris - Luiz, Denis Prudêncio (2011)
CHAPTER 2: Antimicrobial peptides (AMPs) are part of the immune defense that insects have developed to protection hymnoptera against pathogens. This work was done the expression of antimicrobial peptide Abaecina of Apis mellifera in fungi Pichia pastoris. A gene containing elements for cloning, purification and termination of translation was designed based on the sequence of Apis mellifera abaecina then was optimization of codons and subsequent chemical synthesis of the gene. This gene was cloned into pUC57 and after sequencement for confirmation, then the insert was subcloned into expression vector pPIC9 and realized the transformation into Pichia pastoris. After selection of positive clones expression was induced by adding methanol. The supernatant was analyzed at different times to determine the optimum time of production of the recombinant peptide. The growth inhibition test showed that there was significant inhibition of growth of the bacterium Escherichia coli DH5α in time of 24 hours at concentrations of 10 and 25 mg of peptide. The results showed that the peptide abaecina of Apis mellifera produced in Pichia pastoris has antimicrobial activity.